A note on controllability of neutral Volterra integrodifferential systems. (1993) - Balachandran Balachandran, K. K.; Balasubramaniam Balasubramaniam, P. P.
Abstract : Sufficient conditions for the controllability of nonlinear neutral Volterra integrodifferential systems are established. The results are obtained using the Schauder fixed point theorem.